2019
DOI: 10.1001/jamaneurol.2019.2462
|View full text |Cite
|
Sign up to set email alerts
|

Association of Extracellular Vesicle Biomarkers With Alzheimer Disease in the Baltimore Longitudinal Study of Aging

Abstract: IMPORTANCE Blood biomarkers able to diagnose Alzheimer disease (AD) at the preclinical stage would enable trial enrollment when the disease is potentially reversible. Plasma neuronal-enriched extracellular vesicles (nEVs) of patients with AD were reported to exhibit elevated levels of phosphorylated (p) tau, Aβ42, and phosphorylated insulin receptor substrate 1 (IRS-1). OBJECTIVE To validate nEV biomarkers as AD predictors. DESIGN, SETTING, PARTICIPANTS This case-control study included longitudinal plasma samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
193
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 183 publications
(207 citation statements)
references
References 50 publications
11
193
1
2
Order By: Relevance
“…EV purification of immunoprecipitated EVs was confirmed by western blots showing enrichment for transmembrane and intravesicular EV markers (i.e. CD81 and alix), low levels of apolipoprotein A1 and absence of the Golgi-specific negative EV marker GM-130, in comparison with EV-depleted plasma and total EVs, as previously seen (27) (Fig. S1c).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…EV purification of immunoprecipitated EVs was confirmed by western blots showing enrichment for transmembrane and intravesicular EV markers (i.e. CD81 and alix), low levels of apolipoprotein A1 and absence of the Golgi-specific negative EV marker GM-130, in comparison with EV-depleted plasma and total EVs, as previously seen (27) (Fig. S1c).…”
Section: Resultssupporting
confidence: 78%
“…The role of EVs in the brain is multifaceted and includes the exchange of cargo molecules between neurons and glia to regulate neuronal activity (22), but also the transfer of misfolded α-synuclein, A, and hyperphosphorylated tau, possibly contributing to neurodegenerative disease propagation (23,24). We and others have isolated neuronal and astrocytic originenriched EVs (NEVs and AEVs, respectively) from plasma and human cells by particle precipitation followed by immunocapture with anti-GLAST and anti-L1CAM antibodies respectively and have shown that they are carriers of AD pathogenic proteins (25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive and irreversible decline in cognition (Kapogiannis et al, 2019). It accounts for approximate twothirds of all dementias with an increasing morbidity (Prince et al, 2013) and heavy burden of finance (Reitz and Mayeux, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies have used peripheral biomarkers to proxy brain processes, relying on the assumption that peripheral and brain immune activation are correlated (or that peripheral measures are reliable indicators of central processes), which has important limitations. A recent innovation is the use of blood extracellular vesicles (EVs) enriched for neuronal origin (NEVs) as a source of biomarkers that directly reflect neuronal-specific processes [19][20][21][22][23]. Extracellular vesicles (including exosomes) are membranous particles that are continuously released by virtually all cells, including neurons [24].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular vesicles (including exosomes) are membranous particles that are continuously released by virtually all cells, including neurons [24]. They can cross the blood-brain barrier and be preferentially isolated from peripheral blood, through immunocapture with antibodies against neuronal markers, most commonly L1 Cell Adhesion Molecule (L1CAM), a procedure that offers a multi-fold enrichment in neuronal cargo [19][20][21][22][23]. Extracellular vesicles contain cargo that reflects the content of the vesicle's cellular origin, providing a novel avenue for probing intracellular signaling processes including neuroinflammatory pathways that are putatively implicated in neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%